Determination of the Main Performance Indicators of a Forced-Action Concrete Mixer Using Similarity Criteria - Blazko, Vladimir; Anishchenko, Anna; Kostenko, Stanislav; Gerasymenko, Volodymyr (Academic journal Industrial Machine Building Civil Engineering, 2023)
The study focuses on the improvement of a forced-action concrete mixer designed for the preparation of low-workability concrete mixtures. The methodology is based on the application of dimensionless similarity criteria and mathematical modeling. Analytical dependencies for calculating the output rate and drive power were derived based on the geometric and kinematic parameters of the mixer, considering the dynamics of multi-loop mixing. The obtained results enable model scaling without the need for full-scale testing. Further research is planned to optimize operational modes for continuous mixing machines
Keywords: concrete mixer; drive power; energy consumption; forced-action mixing; low-workability mixture; output rate; similarity criteria